"Things I’ve Been Silent about, Memories ", by author Azar Nafisi and "The Foreigner", by author Alia Mamdouh : A Comparative Analytical Study - Abbas, PhD Fala Hassen; Essa, Dr. Thaer.F. Essa (Thi Qar Arts Journal, 2021)
The research deals with two biographies of two different languages, the biography of the Iraqi writer Alia Mamdouh, which bore the title The Foreigner, and the biography of the Iranian writer Azar Nafisi, which bore the title of Things I Was Silent About .the two writers belong to the realist doctrine by reporting stories of fictional events, specifically the critical school that deals, in a critical manner, with the woes and faults that arise on the surface of society. Nafisi is well-known for her fictional and fictional works, so the Iraqi writer Alia Mamdouh is a peer in terms of her abundance of literary works, style and unity of subject. The two writers were bored by the trouble of alienation, the anguish of separation and distance from the homeland, and this was clearly reflected in their effects. Women and their issues are the most important topics covered by the two writers in their work, and they reject the prevailing traditions in their societies. Both writers relied on memory in reporting and recording events.